Obesity and overweight – epidemy of the 21st century - Pupek-Musialik, Danuta; Kujawska-Łuczak, Magdalena; Bogdański, Paweł (Przewodnik Lekarza/Guide for GPs, 2008)
Obesity is a continuously growing health problem of today’s civilisation. Two out of three adults in Poland are obese or overweight. Obesity is not a unitary disease and its causes are multifactorial, including polygenic, metabolic, psychosocial and environmental factors. The adverse health consequences associated with obesity include type 2 diabetes, lipid disorders, arterial hypertension, coronary heart disease, sleep apnoea, arthrosis, and some cancers. We discuss current guidelines on non-pharmacological treatment of obesity and present modern anorectic drugs.